2020
DOI: 10.3390/healthcare8030193
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Family Caregivers of Persons with Dementia: Systematic Review and Meta-Analysis

Abstract: Social and healthcare problems associated with dementia not only affect those who suffer from this disease, but their caregivers as well. The purpose of this study was to analyze the efficacy of mindfulness intervention on psychological variables of caregivers of persons with dementia. A search for scientific articles published from 2000 to 2019 in the PubMed, Web of Science and PsycINFO databases found a total of 282 articles. After screening with preestablished inclusion criteria, ten studies with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…As a result, individuals naturally increase their ability to cope with adverse emotional events, generating a great sense of emotional balance and well-being [8,9]. Furthermore, this self-awareness in clinical practice reduces stress and burnout symptoms, and increases well-being and compassion among clinicians and patients [16,27,28]. According to empirical research, MBIs contribute to significantly reducing emotional exhaustion [8,9,[15][16][17][18]21], depersonalization [8,9,16,17,20,21], and increase the sense of personal accomplishment in PHCP [8,9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, individuals naturally increase their ability to cope with adverse emotional events, generating a great sense of emotional balance and well-being [8,9]. Furthermore, this self-awareness in clinical practice reduces stress and burnout symptoms, and increases well-being and compassion among clinicians and patients [16,27,28]. According to empirical research, MBIs contribute to significantly reducing emotional exhaustion [8,9,[15][16][17][18]21], depersonalization [8,9,16,17,20,21], and increase the sense of personal accomplishment in PHCP [8,9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although systematic reviews and meta-analyses of this topic have been undertaken previously, their results are inconsistent (Liu et al, 2017;Molero Jurado et al, 2020). A review by Molero Jurado et al (2020) showed a significant reduction in caregiver's anxiety and burden.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Although systematic reviews and meta-analyses of this topic have been undertaken previously, their results are inconsistent (Liu et al, 2017;Molero Jurado et al, 2020). A review by Molero Jurado et al (2020) showed a significant reduction in caregiver's anxiety and burden. The present study attempted to investigate anxiety and burden of caregivers (Liu et al, 2017) and performed subgroup analysis of the effects of the intervention's delivery duration on depression, which was not attempted in previous reviews (Collins & Kishita, 2019;Liu et al, 2017;Molero Jurado et al, 2020).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Mindfulness-based interventions are also potentially scalable (because they can be accessed through a smartphone) and can decrease caregiver burden, stress, anxiety, and depression. 68 , 69 However, these interventions should be considered in combination with treatments for depression and other neuropsychiatric symptoms, as well as with assessments of vulnerable situations, an obstacle that is imperative to overcome. Common repositories of resources that can be useful for caregivers in different LACs are needed.…”
Section: Short-term Regional Strategiesmentioning
confidence: 99%